The Spectrum of Haemoglobinopathies: A Tertiary Care Hospital Experience - Noorulain; Aman, Saba; Jamal Siddiqi, Muhammad Younus; Ali, Aisha; Kousar, Shazia; Fatima, Ghulam (Indus Journal of Bioscience Research, 2025)
Background: A scientist, Csaba Harvath first described high-performance chromatography (HPLC). HPLC method is beneficial for detecting different types of hemoglobinopathies, including both quantitative and qualitative disorders of globin chains.This study aimed to explore the significance of HPLC technique in the diagnosis of various hemoglobinopathies. Methods: This cross-sectional retrospective study was conducted in the Central Laboratory of Civil Hospital Karachi from 1st Jan 2021 to 31 Dec 2023. A total of 1464 patients were included who came with low hemoglobin levels. Analysis of blood for complete blood count was done on an XN 1000 analyzer and then HPLC was performed on an Arkray analyzer in samples received in our laboratory. Hemoglobinopathies were diagnosed by the more sensitive method, High-Performance Liquid Chromatography (HPLC) on the analyzer ADAMS A1C Model No. HA-8180T Arkray/Japan. Results: Out of 1464 cases, 1022 (69.8%) were normal, and 442 (30.1%) cases had abnormal haemoglobin pattern. 688(46.9%) were males and 776 (53.0%) were females. Out of 1022 cases of Anemia, 557 (54.5%) were microcytic hypochromic, 45(4.4%) macrocytic, and the rest 421(41.1%) had a normocytic normochromic picture. Of the total cases, 442 (30.1%) showed abnormal Hb fractions. The major abnormality observed was high HbA2. Other hemoglobinopathies in descending order of frequency were Hb D Disease at 40 (9.0%), sickle cell disease at 29 (6.5%), Hb E at 18(4.0%), Sickle/beta-thalassemia in 06 (1.3%), and Hb C 01 (0.2%). Conclusion: Our study revealed a higher frequency of the Beta Thalassaemia trait. It is suggested that detection of HbA2 should be carried out in all the high-risk groups with anaemia. Further larger studies are needed to screen our population to detect thalassaemia carrier state and Iron deficiency Anaemia.